Examining the Practicality of Mobile-Based Gamification Assessment in Electrical Machine Course: A Study in Industrial Electrical Engineering - Doni Tri Putra Yanto; Ganefri Ganefri; Sukardi Sukardi; Rozalita Kurani; Jelpapo Putra Yanto (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
Mobile-based gamification learning is increasingly popular for enhancing student interest and motivation in the learning process, including its application in evaluating learning outcomes. However, the practicality of its use, from the perspective of students as users, needs further evaluation. This study aims to assess the practicality of mobile-based gamification assessment (M-BGA) in evaluating student learning outcomes in the Electrical Machine Course (EMC). M-BGA was developed using Kahoot! application. A survey-based quantitative research design was employed, using the Practicality Assessment Instrument (PAI) as the data collection tool. The practicality of M-BGA was evaluated based on student assessments after its implementation in an EMC. This research involved 83 second-year students from the Industrial Electrical Engineering Study Program, Faculty of Engineering, Universitas Negeri Padang, Indonesia. The results indicate a high level of practicality in several aspects. The Ease of Use aspect scored 92.23% (highly practical), the Reliability aspect scored 89.82% (highly practical), the Student Engagement aspect scored 88.55% (highly practical), and the Learning Impact aspect scored 90.19% (highly useful). Overall, based on student responses, the M-BGA proved to be highly practical in evaluating student learning outcomes in the EMC. M-BGA can serve as an alternative approach for assessing student learning outcomes with an innovative approach.